Progression of Fatigue in Early Parkinson’s Disease: A 3-Year Prospective Cohort Study - Ou, Ruwei; Hou, Yanbing; Liu, Kuncheng; Lin, Junyu; Jiang, Zheng; Wei, Qianqian; Zhang, Lingyu; Cao, Bei; Zhao, Bi; Song, Wei; Shang, Huifang (Frontiers in Aging Neuroscience, 2021)
Objective: To explore the frequency, evolution, associated factors, and risk factors of fatigue over 3-year of prospective follow-up in a cohort of patients with early Parkinson’s disease (PD). Methods: A total of 174 PD patients in the early stage were enrolled and quantitively assessed motor and non-motor symptoms using comprehensive scales including the Fatigue Severity Scale (FSS) annually. Each subject was categorized as PD with and without fatigue based on a cut-off mean value of 4 using FSS. The generalized estimating equation was utilized to investigate the associated factors, and the stepwise binary logistic regression model was performed to explore the predictors. Results: The frequency of fatigue was slightly changed (ranging from 35.1% to 40.4%) during the 3-year follow-up. The changed pattern of the frequency of fatigue was similar to that of anxiety. Fatigue was significantly associated with nocturnal sleep disorders (B 2.446, P<0.001), high Hamilton Anxiety Rating Scale (HAMA) score (B 1.072, P=0.011), and high Unified PD Rating Scale (UPDRS) III score (B 1.029, P=0.003) over time. High UPDRS III score (odds ratio [OR] 1.051, P=0.015) at baseline increased the risk of developing fatigue after 1-year; high LEDD (OR 1.002, P=0.037) increased the risk of developing fatigue after 2-year; and high LEDD (OR 1.003, P=0.049) and high HAMA score (OR 1.077, P=0.042) increased the risk of developing fatigue after 3-year. Conclusions: Our present study provided evidence of the longitudinal evolution of fatigue in patients with early PD and help clinical management of fatigue.